Gradniki močnostne elektronike: pregled - Čučej, Žarko (Informacije MIDEM, 2001)
The PEBB program, sponzored by the Office of Naval Research, seeks to develop a general-purpose power controller capable of performing numerous electrical power conversion functions simply through software reconfiguration.
Keywords: elektronska vezja; inverterji; krmiljenje; močnostna elektronika